Test–Retest Reliability and Random Measurement Error of the Multifactorial Memory Questionnaire in Older Adults With Subjective Memory Complaints - Hui-Ling Yang PhD; Kuei-Ru Chou PhD, RN; Shih-Chieh Lee PhD; Po-Han Lin PhD; Hsin-Yu Chiang PhD (Gerontology and Geriatric Medicine, 2023)
To examine the psychometric properties of the Multifactorial Memory Questionnaire (MMQ) in older adults with subjective memory complaints. The three MMQ subscale (Satisfaction, Ability, and Strategy) was administered twice, with a 3-month interval. The test - retest reliability was examined using intraclass correlation coefficients (ICCs). The random measurement error was examined by calculating the standard error of measurement (SEM) and minimal detectable change (MDC 95 ). The test - retest reliabilities of the three MMQ subscales were generally acceptable. The SEM of the three MMQ subscales was higher than the acceptable criterion of 10%. Despite the influence of random measurement error, the change scores of the three MMQ subscales may represent true changes if they are larger than the MDC 95 of 13.2 (Satisfaction), 18.4 (Ability), and 16.9 (Strategy). The MMQ appears to be a reliable measure for use in research settings, but may not yet be suitable for clinical use.